Commercially available blood storage containers. Issue 1 (16th September 2013) - Prowse, C. V.; de, D.; Hess, J. R.; van der, P. F.; ,
<x xml:space="preserve">Abstract</x> Plastic blood bags improve the safety and effectiveness of blood component separation and storage. Progress towards optimal storage systems is driven by medical, scientific, business and environmental concerns and is limited by available materials, consumer acceptance and manufacturing and regulatory concerns. Blood bag manufacturers were invited to submit lists of the bags they manufacture. The lists were combined and sorted by planned use. The lists were analysed by experts to assess the degree to which the products attend to scientific problems. Specific issues addressed included the use of di‐ethylhexyl phthalate (DEHP) as plasticizer for polyvinyl chloride (PVC) blood bags, the size, material and thickness of platelet bags, and the fracture resistance of plasma bags. Alternatives to DEHP for red blood cell (RBC) storage exist, but are mostly in a developmental stage. Plastic bags (DEHP‐free, PVC‐free) for platelet storage with better gas diffusion capabilities are widely available. Alternatives for plasma storage with better fracture resistance at low temperatures exist. Most RBC products are stored in DEHP‐plasticized PVC as no fully satisfactory alternative exists that ensures adequate storage with low haemolysis. A variety of alternative platelet storage systems are available, but their significance – other than improved oxygen transport – is poorly understood. The necessity to remove DEHP from blood bags still needs to be determined.